2013
DOI: 10.1002/eet.1631
|View full text |Cite
|
Sign up to set email alerts
|

Leveling the Playing Field: Fostering Collaborative Governance Towards On‐Going Reconciliation

Abstract: This paper looks at the potential for collaborative governance for land and resources to become a form of on‐going reconciliation in societies transitioning from past oppression and on‐going social injustice. Structural violence in the form of capacity disparities and policy configuration are explored in order to frame the discussion. Canada and South Africa are presented as two countries that have been going through different experiences in terms of transition, but have had similar experiences in regards to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The use of the anticolonial CGR framework identified that their engagement goals revolved largely around the potential benefits for their climate action as well as the potential to support efforts to advance reconciliation. These findings mirror well‐documented benefits of collaborative environmental governance and its potential to augment policy‐making and support reconciliation between Indigenous Peoples and settlers (Zurba, 2014). Despite these reasons for collaboration, a web of factors and colonial structures and values persist and manifest as barriers to engagement.…”
Section: Discussionsupporting
confidence: 75%
“…The use of the anticolonial CGR framework identified that their engagement goals revolved largely around the potential benefits for their climate action as well as the potential to support efforts to advance reconciliation. These findings mirror well‐documented benefits of collaborative environmental governance and its potential to augment policy‐making and support reconciliation between Indigenous Peoples and settlers (Zurba, 2014). Despite these reasons for collaboration, a web of factors and colonial structures and values persist and manifest as barriers to engagement.…”
Section: Discussionsupporting
confidence: 75%
“…Second, water (and land) management to control for water quality and quantity within a watershed will be more efficient when coordinated between and among watershed groups, actors, and organizations, including First Nations, Métis, and Indigenous organizations (Noble, 2016;Udofia et al, 2016). Last, and perhaps most significant, watershed planning provides a pathway toward reconciliation (Castleden et al, 2017;Truth & Reconciliation Commission of Canada, 2015;Zurba, 2014). The potential for trust and reciprocity between ENGOs, government, industry, and Indigenous communities remains largely unexplored under both of Saskatchewan's watershed planning models.…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing the limits of my own non-Indigenous perspective, I confess that the findings of this research have left me hopeful that multilevel resource governance can promote forms of collaborative decision making that go beyond the more narrowly focussed technical and regulatory engagements of comanagement regimes (for similar conclusions, see Bowie, 2013;Zurba, 2013). It is clearly a positive sign that public government in the NWT, and most particularly the GNWT, is seeking ways to proactively respect nationally and internationally enshrined Indigenous rights by working directly with Indigenous governments as counterparts in multilevel policy dialogue (see also Beck, 2016 on this point).…”
Section: Conclusion: the Complex Dance Of Multilevel Governance And mentioning
confidence: 96%
“…Curiously, there are only weak links between this scholarship and the literature on MLG in relations between Indigenous Peoples and colonial states (one notable exception is Larson & Lewis-Mendoza, 2012). Instead, these themes come together within the rubric of collaborative or participatory governance of natural resources (see for example Black & McBean, 2016;Bowie, 2013;Denny & Fanning, 2016;Dokis, 2015;McGregor, 2014;von der Porten, de Loë, & Plummer, 2015;Zurba, 2013), often linked to a longer-running literature on co-management (see for example Cundill, Thondhlana, Sisitka, Shackleton & Blore, 2013;Feit, 2005;Goetze, 2005;McGregor, 2011;Mulrennan & Scott, 2005;Natcher, Davis & Hickey, 2005;Stevenson, 2006;Zurba et al, 2012). Notions of collaboration and participation are certainly relevant to the present analysis, and co-management is a central facet of the broader environmental governance relationships I aim to discuss.…”
Section: Indigenous Rights and Multilevel Governance In Canadamentioning
confidence: 99%
See 1 more Smart Citation